Pengaruh E-WOM, Citra Merek, E-Commerce, dan Beauty Vlogger terhadap Keputusan Pembelian - Totok Wahyu Abadi; Elviena Fitriana Hawa (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2024)
Social media can currently be used to promote products with beauty vloggers as skincare brand ambassadors. This study aims to analyze and explain the effect of e-WOM, brand image, e-commerce, and beauty vloggers on consumer purchasing decisions for Scarlett Whitening products. This research method uses explanative quantitative. Simple random sampling was applied to collect data from 210 Scarlett Whitening user respondents in East Java through an online questionnaire. The results showed that the e-WOM, brand image, e-commerce, and beauty vlogger variables simultaneously had a significant effect on consumer purchasing decisions for Scarlett Whitening products.